Method for preparing carbon-coated high-entropy alloy through photo-reduction method
The preparation of carbon-covered high-entropy alloys through photoreduction has solved the problems of complex preparation, high cost and insufficient performance of existing high-entropy alloy catalysts, and achieved high stability and durability. It is suitable for hydrogen production and fuel cells such as water decomposition and hydrogen production and fuel cells. field.
Patent Information
- Application Number
- CN202411287208.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing high entropy alloy catalyst preparation methods are complex, costly, insufficient catalytic performance, and poor stability and durability in electrochemical applications.
The carbon coated high-entropy alloy is prepared by photoreduction method, and carbon quantum dots are used as photosensitizers and conductive carbon materials as charge transfer additives. The transition metal salt and conductive carbon materials are mixed under the light source to form a carbon coated high-entropy alloy , reduce particle size and provide antioxidant protection.
It significantly improves the stability and durability of the catalyst, inhibits the reverse reaction of water decomposition, improves catalytic activity and cycle stability, and is suitable for water decomposition hydrogen production and fuel cells.
Smart Images

Figure CN119140816A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemistry, and in particular to a carbon-coated high-entropy alloy and a photoreduction preparation method thereof. Background Art
[0002] At present, high-performance catalysts are key materials for water decomposition, hydrogen production, fuel cells, pollutant purification, organic reactions, etc. The amount of precious metals used is large, and they are easily oxidized, agglomerated, and induce reverse reactions or side reactions of the target reaction in the catalytic reaction, resulting in expensive catalyst costs and limiting the performance of the catalyst. CN118086948A discloses a porous high-entropy alloy catalytic electrode based on a B2-BCC structure, a preparation method thereof, and an acidic oxygen evolution application. The composition of the catalytic electrode is designed to be composed of a high-entropy alloy formed by a B2 structure forming component A, a refractory metal passivation component M, and a precious metal active component Q; the high-entropy alloy is AxMyQz; A is selected from at least two of Ni, Ti, Al and Fe, M is selected from at least one of Ta, Nb, Hf, W and Mo, and Q is selected from at least two of Ir, Os, Ru and Pt. Under the condition that the B2 phase composed of Ni and Ti is selectively corroded, a three-dimensional bicontinuous through-hole structure is formed on the surface of the catalytic electrode, and the pore size is 0.5-2μm. CN118028930A discloses a method for preparing a high entropy alloy coating catalyst by pulse electrodeposition, which reduces or eliminates the concentration polarization at the cathode interface by controlling the parameters such as the pulse electrodeposition waveform, frequency, on-off ratio and average current density, and uses a multi-component complexing agent to couple the pulse electrodeposition technology to achieve multi-element co-deposition. CN118002144A discloses a method for preparing a copper-based high entropy alloy Fenton-like catalyst based on a controllable electrodeposition method, wherein a pure copper electrode is selected as the cathode and a graphite electrode is selected as the anode. The cathode and the anode are used to make an electrodeposition device, and the copper-based high entropy micro-nano alloy powder is deposited on the electrode cathode. CN117798357A discloses a method for preparing palladium-ruthenium-based high entropy alloy nanosheets by thermal reduction of a palladium source, a ruthenium source, an auxiliary metal precursor (the auxiliary metal precursor contains at least one carbonyl salt), a reducing agent and cyclohexane-ethanol mixture. CN117965919A discloses a method for preparing a carbon-supported platinum group metal-based high entropy alloy by a 200°C hydrothermal method. CN117737772A discloses a method for preparing a stainless steel pole net for electrolytic hydrogen production based on etching activation, vapor deposition and alloy forming. CN118073586A discloses a method and application for preparing a high entropy alloy by pyrolysis of a metal organic framework material and impregnation with a loaded transition metal. CN117936821A discloses a tetragonal platinum iron nickel copper based high entropy alloy catalyst and its gram-level preparation method and application, wherein the preparation method is liquid phase ultrasonic dispersion + grinding + calcination of a metal precursor and a carbon carrier. CN117966191A discloses a method for depositing a high entropy alloy film on a conductive substrate material by a pulsed laser deposition method. CN117702175A discloses a method for preparing a nanoporous high entropy alloy / hydroxy oxide electrocatalyst by a high entropy alloy net, dealloying treatment and surface activation treatment.CN117983214A discloses a method of mixing a soluble metal salt solution with a reducing agent and a flocculant, heating and melting the mixture to obtain a preheated reduced phase, then injecting a metal precursor solution into the preheated reduced oil phase to obtain a catalyst crude particle, and post-treating the catalyst crude particle to obtain a high entropy alloy particle. CN117894937A discloses a method of preparing a high entropy alloy-loaded graphene oxide composite material by a hydrothermal method and calcining in a reducing atmosphere and its application. CN117718485A prepares nitrogen-doped carbon-coated copper-nickel-iron-cobalt-chromium-titanium high entropy alloy nanospheres by ball milling and direct current arc discharge reaction of six metal mixed powders in equal molar ratios. CN117680690A prepares a nanoscale high entropy alloy electrocatalyst by loading the nanoscale high entropy alloy obtained by heat-treating the precursor on a conductive carrier XC-72. CN117463362A prepares a carbon-based high entropy alloy catalyst by loading high entropy alloy nanoparticles on the surface of a carbon-based material by one-pot reduction combined with high temperature annealing.
[0003] The challenges faced by existing methods in preparing high-entropy alloy catalysts include complex preparation processes, high costs, insufficient catalytic performance, and stability and durability in electrochemical applications.
[0004] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0005] The main purpose of the present invention is to solve the problems existing in the above-mentioned background technology and provide a method for preparing carbon-coated high entropy alloy by photoreduction method.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a carbon-coated high entropy alloy by a photoreduction method comprises the following steps:
[0008] (a) dissolving carbon quantum dots and transition metal salt in anhydrous ethanol to prepare solution A;
[0009] (b) dispersing the conductive carbon material into the solution A of step (a) to prepare a dispersion B;
[0010] (c) irradiating the dispersion B obtained in step (b) under a light source for 0.5 to 6 hours to obtain a dispersion C;
[0011] (d) centrifugally separating the dispersion C obtained in step (c) to obtain a solid, and washing the solid to obtain a carbon-coated high entropy alloy.
[0012] Further:
[0013] In step (a), the weight ratio of carbon quantum dots: transition metal salt calculated as metal: ethanol is 1:0.01 to 1:4 to 50.
[0014] In step (a), the transition metal salt is selected from chlorides, nitrates, sulfates, acetates and mixtures thereof, preferably chlorides.
[0015] In step (a), the transition metal is selected from Fe, Co, Ni, Cu, Ag, Au, Pt, Rh, Pd, Ir, Ru, and Os.
[0016] In step (b), the conductive carbon material is selected from graphene, carbon nanotubes, carbon black, Ketjen black, and acetylene black.
[0017] In step (b), the amount of the conductive carbon material used is 1 to 20 times the weight of the carbon quantum dots.
[0018] In step (c), the light source is selected from light with a wavelength of 200nm to 2000n and a power of 10 to 2000W.
[0019] The light source is sunlight or a xenon lamp simulating sunlight.
[0020] A carbon-coated high-entropy alloy is prepared by a photoreduction method. The alloy is prepared by the method for preparing a carbon-coated high-entropy alloy by a photoreduction method.
[0021] The present invention has the following beneficial effects:
[0022] The present invention provides a method for preparing a carbon-coated high-entropy alloy by a photoreduction method, wherein carbon quantum dots are used as photosensitizers, and conductive carbon is used as a charge transfer aid and a carrier of transition metals. During the photoreduction process, the carbon dots are polymerized on the surface of the high-entropy alloy, which can simultaneously reduce the particle size of the high-entropy alloy and protect the high-entropy alloy from oxidation. In the catalytic reaction, the reverse reaction of water decomposition can be inhibited, thereby improving the stability of the catalyst in catalytic reactions such as water decomposition reactions, and has significant practical value.
[0023] The preparation method of the present invention can realize amorphous carbon coating of high entropy alloy nanoparticles or atomic clusters, significantly improving the catalytic activity and durability of precious metals. The product is particularly suitable for fields such as water decomposition hydrogen production and fuel cells, and can inhibit the reverse water decomposition reaction on the surface of precious metals, and has the characteristics of high catalytic activity and good cycle stability. The prepared product can be applied to water decomposition hydrogen production, fuel cells and other fields involving precious metal catalysis.
[0024] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 TEM+EDS mapping diagram of Example 1 of the present invention;
[0026] Figure 2 TEM+EDS mapping diagram of Example 2 of the present invention;
[0027] Figure 3 0.5MH in Example 1 of the present invention 2 SO 4 HER performance diagram in electrolyte;
[0028] Figure 4 0.5MH in Example 1 of the present invention 2 SO 4 Diagram of OER performance in electrolyte. DETAILED DESCRIPTION
[0029] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0030] The embodiment of the present invention provides a method for preparing a carbon-coated high entropy alloy by a photoreduction method, comprising the following steps:
[0031] (a) dissolving carbon quantum dots and transition metal salt in anhydrous ethanol to prepare solution A;
[0032] (b) dispersing the conductive carbon material into the solution A of step (a) to prepare a dispersion B;
[0033] (c) irradiating the dispersion B obtained in step (b) under a light source for 0.5 to 6 hours to obtain a dispersion C;
[0034] (d) centrifugally separating the dispersion C obtained in step (c) to obtain a solid, and washing the solid to obtain a carbon-coated high entropy alloy.
[0035] In some embodiments, in step (a), the weight ratio of carbon quantum dots: transition metal salt calculated as metal: ethanol is 1:0.01 to 1:4 to 50.
[0036] In some embodiments, in step (a), the transition metal salt is selected from chlorides, nitrates, sulfates, acetates and mixtures thereof, preferably chlorides.
[0037] In some embodiments, in step (a), the transition metal is selected from Fe, Co, Ni, Cu, Ag, Au, Pt, Rh, Pd, Ir, Ru, and Os.
[0038] In some embodiments, in step (b), the conductive carbon material is selected from graphene, carbon nanotubes, carbon black, Ketjen black, and acetylene black.
[0039] In some embodiments, in step (b), the amount of the conductive carbon material used is 1 to 20 times the weight of the carbon quantum dots.
[0040] In some embodiments, in step (c), the light source is selected from light with a wavelength of 200nm to 2000n and a power of 10 to 2000W.
[0041] In some embodiments, the light source is sunlight or a xenon lamp simulating sunlight.
[0042] The embodiment of the present invention also provides a carbon-coated high-entropy alloy prepared by a photoreduction method, which is prepared by the method for preparing a carbon-coated high-entropy alloy by a photoreduction method.
[0043] The present invention prepares carbon-coated high-entropy alloys by adopting a photoreduction method, ingeniously utilizing carbon quantum dots as photosensitizers and conductive carbon as charge transfer aids and carriers of transition metals, and realizes effective polymerization of carbon dots on the surface of high-entropy alloys during the photoreduction process. This innovative method not only reduces the particle size of the high-entropy alloy, but also provides antioxidant protection for the high-entropy alloy, thereby effectively inhibiting the reverse reaction of water decomposition in the catalytic reaction. The catalyst thus prepared exhibits excellent catalytic activity and cycle stability in applications such as water decomposition to produce hydrogen and fuel cells, significantly improves the use efficiency and durability of precious metals, ensures the high performance and long-term effectiveness of the catalyst, and demonstrates the significant practical value and broad application prospects of the present invention in the field of precious metal catalysis.
[0044] The specific embodiments of the present invention are further described below.
[0045] Example 1
[0046] Dissolve 50 mg of carbon dots in 5 ml of anhydrous ethanol, and then evenly mix chloroauric acid, platinum chloride, palladium chloride, nickel chloride, cobalt chloride, ruthenium chloride, yttrium chloride, and rhodium chloride with the carbon dot ethanol solution in a molar ratio of 1:1:1:1:1:1:1:1 (the total weight of precious metals is 10 wt.% of the weight of carbon dots). Then add 0.5 g of CNT and stir for 30 min. Then transfer the mixture to a xenon lamp light source for irradiation for 30 min. Then wash and dry the obtained solid to obtain an octa-catalyst (catalyst 1).
[0047] Example 2
[0048] 50 mg of carbon dots were dissolved in 5 ml of anhydrous ethanol, and then chloroauric acid, platinum chloride, nickel chloride, cobalt chloride, ruthenium chloride, and yttrium chloride were uniformly mixed with the carbon dot ethanol solution (the total weight of precious metals was 10 wt.% of the weight of carbon dots) in a molar ratio of 1:1:1:1:1:1, and then 0.5 g of CNT was added and stirred for 30 min. Then, the mixture was transferred to a xenon lamp light source for irradiation for 30 min, and the obtained solid was washed and dried to obtain a hexavalent catalyst (catalyst 2).
[0049] Example 3
[0050] 50 mg of carbon dots were dissolved in 5 ml of anhydrous ethanol, and then chloroauric acid, platinum chloride and ruthenium chloride were uniformly mixed with the carbon dot ethanol solution in a molar ratio of 1:1:1 (the total weight of precious metals was 10 wt.% of the weight of carbon dots), and then 0.5 g of CNT was added and stirred for 30 min. Then, the mixture was transferred to a xenon lamp light source for irradiation for 30 min, and the obtained solid was washed and dried to obtain a ternary catalyst (catalyst 3).
[0051] Example 4
[0052] The steps are the same as those in Example 1, except that 0.5 g of CNT is replaced by 0.5 g of graphene.
[0053] Example 5
[0054] The steps are the same as those in Example 1, except that 0.5 g of CNT is replaced by 0.5 g of carbon black.
[0055] Application Examples
[0056] Electrode preparation: The detailed preparation process of the working electrode is as follows: 5 mg of catalyst powder was dispersed in a mixed solution of 970 μL of ethanol and 30 μL of 5 wt.% Nafion solution, ultrasonically treated for 30 min, and then 200 μL of the evenly dispersed suspension was dropwise dropped on a 1×1.5 cm2 carbon cloth. The catalyst coverage area was maintained at 1 cm2 and was fully dried in the air.
[0057] Figure 1 TEM+EDS mapping of Example 1 of the present invention shows the high entropy cluster catalyst of carbon-coated Ni-Co-Ru-Rh-Pd-Ir-Pt / CNT seven-membered single atom. Figure 1 It can be seen that all metals are evenly dispersed without obvious agglomeration, indicating that a homogeneous high entropy alloy has been formed; Figure 2 TEM+EDS mapping diagram of Example 2 of the present invention shows the preparation of carbon-coated Ni-Co-Ru-Rh-Pd-Ir-Pt / CNT high entropy nanocatalyst based on the photoreduction method of carbon quantum dots. Figure 2 It can be seen that as the components decrease, all metals are evenly dispersed without obvious agglomeration, indicating that the formation of homogeneous high-entropy alloys mainly depends on the rapid and uniform photochemical deposition on the carbon surface, which has nothing to do with the amount of components. Figure 3 is the HER performance diagram of Example 1 of the present invention, Figure 3 As can be seen, at 0.5MH 2 SO 4 HER in electrolyte, reaching 10 mA cm -2The current density only requires an overpotential of 29 mV, and after 10,000 cycles, the performance is still better than that of commercial Pt / C catalysts. Figure 4 is the OER performance diagram of Example 1 of the present invention, Figure 4 As can be seen, at 0.5MH 2 SO 4 OER in electrolytes, reaching 10 mA cm -2 The current density only requires an overpotential of 1.45 mV, and after 20,000 cycles, there is no obvious performance degradation.
[0058] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A method for preparing a carbon-coated high entropy alloy by photoreduction, characterized in that: The steps include: (a) dissolving carbon quantum dots and transition metal salt in anhydrous ethanol to prepare solution A; (b) dispersing the conductive carbon material into the solution A of step (a) to prepare a dispersion B; (c) irradiating the dispersion B obtained in step (b) under a light source for 0.5 to 6 hours to obtain a dispersion C; (d) centrifugally separating the dispersion C obtained in step (c) to obtain a solid, and washing the solid to obtain a carbon-coated high entropy alloy.
2. The method for preparing a carbon-coated high entropy alloy by photoreduction as claimed in claim 1, characterized in that: In step (a), the weight ratio of carbon quantum dots: transition metal salt calculated as metal: ethanol is 1:0.01 to 1:4 to 50.
3. The method for preparing a carbon-coated high entropy alloy by photoreduction as claimed in claim 1 or 2, characterized in that: In step (a), the transition metal salt is selected from chlorides, nitrates, sulfates, acetates and mixtures thereof, preferably chlorides.
4. The method for preparing a carbon-coated high entropy alloy by photoreduction according to any one of claims 1 to 3, characterized in that: In step (a), the transition metal is selected from Fe, Co, Ni, Cu, Ag, Au, Pt, Rh, Pd, Ir, Ru, and Os.
5. The method for preparing a carbon-coated high entropy alloy by photoreduction according to any one of claims 1 to 4, characterized in that: In step (b), the conductive carbon material is selected from graphene, carbon nanotubes, carbon black, Ketjen black, and acetylene black.
6. The method for preparing a carbon-coated high entropy alloy by photoreduction according to any one of claims 1 to 5, characterized in that: In step (b), the amount of the conductive carbon material used is 1 to 20 times the weight of the carbon quantum dots.
7. The method for preparing a carbon-coated high entropy alloy by photoreduction method according to any one of claims 1 to 6, characterized in that: In step (c), the light source is selected from light with a wavelength of 200nm to 2000n and a power of 10 to 2000W.
8. The method for preparing a carbon-coated high entropy alloy by photoreduction as claimed in claim 7, characterized in that: The light source is sunlight or a xenon lamp simulating sunlight.
9. A method for preparing a carbon-coated high entropy alloy by a photoreduction method, characterized in that: The alloy is prepared by the method for preparing carbon-coated high entropy alloy by photoreduction method as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method and application of carbon-based high-entropy alloy catalyst
CN117463362A
Preparation of nano-scale high-entropy alloy electrocatalyst and application of nano-scale high-entropy alloy electrocatalyst in fully dissolved water
CN117680690A
Nano-porous high-entropy alloy / oxyhydroxide electrocatalyst and preparation method thereof
CN117702175A
Controllable preparation method and application of nitrogen-doped carbon-coated six-element high-entropy alloy nanospheres
CN117718485A
Stainless steel electrode net for electrolytic hydrogen production and preparation method and application of stainless steel electrode net
CN117737772A
Cited By
High-performance nitrogen-containing hard alloy material based on vanadium-titanium rare earth carbonitride solid solution and preparation method thereof
CN119242977A
High performance nitrogen-containing cemented carbide material based on vanadium-titanium carbonitride solid solution and preparation method thereof
CN119242977B
